Some Inequalities of Generalized p-Convex Functions concerning Raina’s Fractional Integral Operators - Changyue Chen; Muhammad Shoaib Sallem; Muhammad Sajid Zahoor (Journal of Mathematics)
Convex functions play an important role in pure and applied mathematics specially in optimization theory. In this paper, we will deal with well-known class of convex functions named as generalized p-convex functions. We develop Hermite–Hadamard-type inequalities for this class of convex function via Raina’s fractional integral operator.